2021
DOI: 10.1021/acs.jmedchem.1c00206
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Dimerization Disruption of Leishmania infantum Trypanothione Reductase by Triazole-phenyl-thiazoles

Abstract: Inhibition of Leishmania infantum trypanothione disulfide reductase ( Li TryR) by disruption of its homodimeric interface has proved to be an alternative and unexploited strategy in the search for novel antileishmanial agents. Proof of concept was first obtained by peptides and peptidomimetics. Building on previously reported dimerization disruptors containing an imidazole-phenyl-thiazole scaffold, we now report a new 1,2,3-triazole-based chemotype that yields nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…Structural cavities in Li TryR dimer and monomer were calculated using the Computed Atlas of Surface Topography of proteins (CASTp) web server [ 32 ] and a probe radius of 1.4 Å. Molecular dynamics simulations were run in the AMBER force field, as described previously for Li TryR dimer and complexes [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The molecular graphics program PyMOL (v. 1.8, Schrödinger, 2015) was employed for molecular editing, visualization, and figure preparation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural cavities in Li TryR dimer and monomer were calculated using the Computed Atlas of Surface Topography of proteins (CASTp) web server [ 32 ] and a probe radius of 1.4 Å. Molecular dynamics simulations were run in the AMBER force field, as described previously for Li TryR dimer and complexes [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The molecular graphics program PyMOL (v. 1.8, Schrödinger, 2015) was employed for molecular editing, visualization, and figure preparation.…”
Section: Methodsmentioning
confidence: 99%
“… ( A ) An illustration of the Li TryR dimer (PDB entry 6I7N [ 27 ]) showing the large channel (yellow) connecting the NADPH entry site to the interfacial cavity [ 28 ], as calculated by the CASTp web server [ 32 ]; ( B ) an illustration of a Li TryR monomer showing a similar channel (yellow, 2016 Å 2 , 2550 Å 3 ) plus a second one (green, 129 Å 2 , 125 Å 3 ) that makes up the putative target site for the dimer-disrupting peptides and SMPCs; ( C ) theoretical model of the complex between prototype peptide TRL38 (C atoms in grey) and a Li TryR monomer (rainbow-colored illustration, with N - and C-termini in blue and red, respectively). …”
Section: Figures Schemes and Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Various chemical structures were reported with TR inhibitor activity and leishmaniacidal activity to the literature: Ag(0) nanoparticles encapsulated by ferritin molecules [89], Cu(II) diketonates [90], oxabicyclo[3.3.1]nonanones [73], azole-based compounds -e. pyrrole [91], β-carboline-quinazolinone hybrid [92], phenothiazine and phenoxazine derived chloroacetamides [93], selenocyanates and diselenide compounds [94,95], iminodibenzyl derivatives with ethylenediamine, ethanolamine and diethylenetriamine and their copper(II) complexes [96], diaryl sulfide derivatives [97], ammonium trichloro [1,2-ethanediolato-O,O′]-tellurat [98], all-hydrocarbon stapled peptides [99] chalcone derivatives [100], thiophene derivatives [101], imidazole-phenyl-thiazole compounds [102], isothiocyanate derivatives [103], (phenylthio)pyrimidin-4-amine derivatives [104], ferrocenylquinoline derivatives [105], triazole-phenyl-thiazoles derivatives [106], fluorene derivatives [107], adamantan derivatives, and their gold complexes [108] and natural products [109,110] (Figure 6).…”
Section: Trypanothione Reductase (Tr Tryr Trypanothione-disulfide Red...mentioning
confidence: 99%
“…In comparison to reference imidazoles, certain compounds with (poly) aromatic substituents significantly improve the capacity to disrupt LiTR dimerization. Revuelto et al, recently revealed symmetrical triazole analogue with a much more potent inhibitory effect was able to kill both external and intracellular parasites [100]. The anti-leishmanial action of various resveratrol analogues (ResAn) was investigated utilizing molecular modeling, computational docking, and in vitro research, with a focus on their pro-oxidant effect.…”
Section: Trypanothione Pathwaymentioning
confidence: 99%